Diphyllobothrium sprakeri n. sp. (Cestoda: Diphyllobothriidae): a hidden broad tapeworm from sea lions off North and South America - Hernández-Orts, Jesús S; Kuzmina, Tetiana A; Gomez-Puerta, Luis A; Kuchta, Roman (Parasites & vectors, 2021)
BACKGROUND: The systematic of several marine diphyllobothriid tapeworms of pinnipeds has been revised in recent years. However, 20 species of Diphyllobothrium from phocids and otariids are still recognized as incertae sedis. We describe a new species of Diphyllobothrium from the intestine of California sea lions Zalophus californianus (Lesson) (type-host) and South American sea lions Otaria flavescens (Shaw). METHODS: Zalophus californianus from the Pacific coast of the USA and O. flavescens from Peru and Argentina were screened for parasites. Partial fragments of the large ribosomal subunit gene (lsrDNA) and the cytochrome c oxidase subunit 1 (cox1) mitochondrial gene were amplified for 22 isolates. Properly fixed material from California sea lions was examined using light and scanning electron microscopy. RESULTS: A total of four lsrDNA and 21 cox1 sequences were generated and aligned with published sequences of other diphyllobothriid taxa. Based on cox1 sequences, four diphyllobothriid tapeworms from O. flavescens in Peru were found to be conspecific with Adenocephalus pacificus Nybelin, 1931. The other newly generated sequences fall into a well-supported clade with sequences of a putative new species previously identified as Diphyllobothrium sp. 1. from Z. californianus and O. flavescens. A new species, Diphyllobothrium sprakeri n. sp., is proposed for tapeworms of this clade. CONCLUSIONS: Diphyllobothrium sprakeri n. sp. is the first diphyllobothriid species described from Z. californianus from the Pacific coast of North America, but O. flavescens from Argentina, Chile and Peru was confirmed as an additional host. The present study molecularly confirmed the first coinfection of two diphyllobothriid species in sea lions from the Southern Hemisphere.
Keywords: střeva; Male; mitochondriální geny; lachtani; fylogeneze; cox1; Phylogeny; Genes, Mitochondrial; Otaria flavescens; difylobotriáza; mužské pohlaví; South America; lsrDNA; Diphyllobothriasis; Animals; ženské pohlaví; Jižní Amerika; Otariidae; zvířata; North America; Helminths; Intestines; Parasites; Sea Lions; Female; Pinnipedia; Zalophus californianus; Diphyllobothrium; Severní Amerika